Calidad del banano en relación al color de la funda en época de verano - Farías Soledispa, Yuri Simón (2009)
In the Hda ¨La Papillo¨ located in the parish Rio Bonito of the canton The Guabo, the formation ecological tropical very dry forest, one carries out the relative project to determine the kindness of the color of case of polyethylene type pin hole about the quality of the export fruit, with the following objectives: 1. to study the effect that has the color of the case protector of the cluster about the final quality of the export fruit. 2. to determine it will be achieved the best indexes of having filled with what case type. The study factor was the color of the case: The cases were treated with clorpirifos, they were of the type pin hole 32 inches wide for 62 inches long, 4 200 holes for square meter 3 mm of diameter and 0,0004 inch of thickness. The witness was the transparent case, also tried with the same insecticide. The variables were: 1.Días to the one filled of the fingers. 2. damages caused by two species, trips of the flower (Franklinella) and (Chaetanophostrips orchiidi) in second o'clock and it finishes hand. 3. damages taken place by the coleopteron in the first and second hand. 4. index of damage taken place by the cochineal presence and or it scales. 5. texture of the bark of the fingers. 6. resistance to the I ruin of the fingers. 7. color of the bark of the fingers. 8. fruit percentage with Speckling. 9. it shrinks. 10. Burns for the sun. The obtained results and analyzed completely by means of the statistical pattern of a Design Randomizado, statistical significancia was not obtained for the treatments to exception from the days to the maturation, damages of Colaspis, cochineal obtained under the conditions of low population of plagues of the cluster study reason. In the period of having filled with the fruit certain reduction of the time was obtained until in one week with cases of blue and gray color. The registered damages by reason of trips of the flower (Franklinella parvola) as of the red stain (Chaetanophostrips sp) they were low. In the protection of the fruit against the damage of Colaspis, it was more efficient with blue and gray cases, overcoming the witness. The quality of the fruit was similar in all treatments, differing if as soon as he/she refers to the ratium that was superior in yellow and gray case overcoming to the conventional witness or transparent case.